Implementasi Kebijakan Sistem Ketahanan Kebakaran Lingkungan Dalam Upaya Pencegahan Kebakaran Dini Pada Kecamatan Cakung Kota Administrasi Jakarta Timur - Wahyono, Tri Hadi; Hendrarso, Panji; Harjo, Joko S Dwi (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2025)
In 2023, East Jakarta recorded the highest number of fire incidents in Jakarta, with 594 cases, of which Cakung District accounted for 126. However, the implementation of the Fire Resilience System in Cakung remains suboptimal, as Fire Volunteer Units have only been established in some community units (RW) across four out of the seven sub-districts. This study aims to analyze and evaluate the implementation of the Fire Resilience System Policy in early fire prevention at the Fire and Rescue Sub-Department of East Jakarta Administrative City. A qualitative approach was employed, with data collected through interviews involving seven informants. The findings indicate that the implementation of the Fire Resilience System Policy at the Fire and Rescue Sub-Department of East Jakarta has been effective and has yielded positive results. However, several challenges persist, including limitations in human resources, fire prevention facilities, inter-agency coordination, public awareness, and budget constraints. To address these challenges, efforts have been made to strengthen human resources through continuous training, improve fire prevention facilities, optimize inter-agency coordination, enhance public awareness and participation, utilize technology for monitoring and early warning systems, and increase collaboration with the private sector and non-governmental organizations.